Feeling Failure: Appnography and Its Affective Ties to the Ethnographer’s Life - Atienza, Paul Michael Leonardo (Ethnoscripts, 2024)
My research seeks to understand queer Filipino men’s digital lives in Manila, the Philippines, and Los Angeles, United States of America. It examines how experiences of failure inform complex negotiations online and offline in the search for connection, especially when feelings are amplified and complicated by social categories of race, ethnicity, class, gender, and sexuality. I apply Rohit K Dasgupta and Debanuj Dasgupta’s assertion from their study participants in India that the sharing of failure in virtual spaces generates different forms of intimate subjectivity forging affective bonds. This essay reflects on failure and disappointment as a prominent topic of ethnographic inquiry and methodological critique but specifically on how the feeling of failure seeped into various parts of the researcher’s life – my writing, my thinking, my belief in myself. It is a feeling that endures. It is a testament to the need for continued ethnographic work, with a caution to the infectious insecurities animating the socialities of dating app relations.